2017
DOI: 10.1039/c7qo00562h
|View full text |Cite
|
Sign up to set email alerts
|

Direct C–H heteroarylation by an acenaphthyl-based α-diimine palladium complex: improvement of the reaction efficiency for bi(hetero)aryls under aerobic conditions

Abstract: A bulky ancenaphthyl skeleton-based α-diimine palladium complex has been developed, which exhibited high reactivity for direct heteroarylation of heteroaryl bromides under aerobic conditions with a broad substrate scope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 85 publications
1
13
0
Order By: Relevance
“…By contrast, direct C-H arylation offers a more atom economic alternative, especially to Suzuki-coupling. [17][18][19][20] The direct arylation approach has already been applied to the synthesis of conjugated polymers; 21 however, it has not yet been adapted to the dispersion polymerization protocol to synthesize narrowly dispersed or uniform conjugated polymer particles.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, direct C-H arylation offers a more atom economic alternative, especially to Suzuki-coupling. [17][18][19][20] The direct arylation approach has already been applied to the synthesis of conjugated polymers; 21 however, it has not yet been adapted to the dispersion polymerization protocol to synthesize narrowly dispersed or uniform conjugated polymer particles.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we performed XPS analysis of the reaction mixture under the standard condition in the presence of catalyst C2 (shown in Figure ). We found four peaks at 336.0 eV and 337.8 eV, 341.2 and 342.9 eV, which assigned of Pd(0) and Pd(II) are present in the reaction mixture , . Further, by TEM analysis of the reaction mixture in the presence of palladium complexes C2 we observed palladium nanoparticles.…”
Section: Resultsmentioning
confidence: 63%
“…The ligand exchange happens with potassium salts of pivalic acid provided intermediate C (Scheme). The C–H bond (C5) cleavage step 1‐methyl‐1H‐imidazole/1,2‐dimethyl‐1H‐imidazole with the aid of pivalate generates intermediate C via CMD transition state, which undergoes reductive elimination giving rise to the arylated product and regenerated Pd(0) intermediate (A).…”
Section: Resultsmentioning
confidence: 99%
“…We also showed that the reaction is feasible when using bromoheteroaryls as coupling partners. Thus, the reaction between 1 and either 3-bromopyridine or 2-bromothiophene led to expected products 11 30a and 12 38 in 69 and 60% yields, respectively (entries 11 and 12, Table 1).…”
Section: Scheme 1 Optimization Of C-h Arylation Of Imidazo[12-a] Pymentioning
confidence: 96%
“…1 H NMR and 13 C NMR spectrum matched that of the literature. -2-yl)imidazo[1,2-a] pyridine 12 38 . The generale procedure afforded 102 mg (60% yield) of the title compound.…”
Section: -Chloro-3-(4-methoxyphenyl)mentioning
confidence: 99%